Critical velocity, lactate concentration and rowing performanc - Emerson Franchini; Fernando de Campos Mello (Universidade Federal de Santa Catarina, 2005)
There is, in the literature, a search for simple and non-expensive tests to determine the intensity equivalent to maximal lactate steady state (MLSS). The critical velocity (CV) has been an indirect method used to determine MLSS. However, the few studies that applied CV in rowing did not verify its validity to estimate MLSS. Therefore, this study had the purposes of testing the validity of CV in determining MLSS velocity as well as of analyzing its predictive value in rowing performance. Therefore, eleven male rowers were submitted to three trials to exhaustion for CV determination. A 2000-m test in a rowing ergometer was used as performance criteria. Later, the subjects performed a continuous test at the CV, with blood lactate concentration (LA) being measured during the test. During the continuous test, the LA linearly increased from rest (2 ± 0.,2 mmol.L-1) to the 10th minute (10.9 ± 3.7 mmol.L-1) with slightly higher values (11.6 ± 2.3 mmol.L-1) at the mean time to exhaustion (10.4 ± 3 min), showing that CV does not correspond to MLSS. The correlation coefficient between CV and mean velocity at the 2000-m test (r = 0.87; p < 0.001) presented the possibility for performance prediction. However, it is important to emphasize that two performance values are being correlated and one of them was determined from distances similar to the 2000-m test. RESUMO Existe, na literatura, a busca por testes simples e baratos para determinar a intensidade equivalente à máxima fase estável do lactato sangüíneo (MFELS). A velocidade crítica (VC) tem sido um dos métodos indiretos utilizados para determinar a MFELS. No entanto, os poucos estudos que utilizaram a VC no remo, não verificaram sua validade para estimar a MFELS. Assim, esse estudo teve como objetivos verificar a validade da VC para determinar a velocidade da MFELS e analisar seu valor preditivo para o desempenho no remo. Para isso, onze atletas de remo do sexo masculino foram submetidos a três estímulos até a exaustão para a identificação da VC. Uma prova de 2000 m no ergômetro de remo foi usada como critério de desempenho. Posteriormente, os sujeitos realizaram um teste contínuo na VC, sendo mensurada a concentração de lactato sangüíneo (LA) no decorrer do teste. Durante o teste contínuo na VC, a LA aumentou linearmente do repouso (2 ± 0,2 mmol.L-1) ao décimo minuto (10,9 ± 3,7 mmol.L-1), com valores ligeiramente superiores (11,6 ± 2,3 mmol.L-1) no momento da exaustão (10,4 ± 3 min), demonstrando que a VC não corresponde à MFELS. A correlação encontrada entre a VC e a velocidade média na simulação da prova dos 2000 metros (r = 0,87; p < 0,001) demonstra a possibilidade de sua utilização para predizer o desempenho. Contudo, é importante ressaltar que estão sendo correlacionados dois valores de desempenho, sendo que um deles foi determinado com base em distâncias similares daquela da prova.